Kolaborasi SMKN 1 Lingsar dan NGO Gema Alam NTB dalam Penerapan Pompa Air Tenaga Surya di Desa Pandan Indah - Akhmad Muji Hartono; Sumardi Sumardi; Achmad Pauji; Andy Tirta; Universitas Darma Persada Ariati (Journal of Empowerment Community, 2026)
The collaborative project between SMKN 1 Lingsar and NGO Gema Alam NTB in Pandan Indah Village aims to implement solar-powered water pump technology as a sustainable solution for clean water supply while supporting Indonesia’s energy transition. Through stages of water needs assessment, system design, installation, operator training, and performance evaluation, a 2.5 kWp PV system with five 500 Wp modules was successfully operated without batteries. The system produced 10–12 kWh/day of energy and pumped 37–61 m³/day of water, meeting daily needs while reducing operational costs by approximately IDR 900,000 per month and lowering CO₂ emissions by about 420 kg. This program not only enhances energy efficiency and rural self-reliance but also provides contextual learning for students and strengthens community empowerment towards sustainable development through green technology innovation.